Enhancing Supply Chain Efficiency Through Blockchain Technology: A Centralized Multi-distributor and Multi-retailer Approach - Motla, Ritu; Saxena, Neha; Kumar, Ashok; Sana, Shib Sankar (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025)DO - 10.2298/YJOR231115026M, 2024)
Blockchain technology has emerged as a transformative solution for supply chain management, offering a myriad of benefits to the industry. This paper explores the potential benefits of incorporating blockchain technology into supply chain management to enhance security and trustworthiness. We present a centralized supply chain system comprising a single manufacturer, multiple distributors, and multiple retailers. Geographical divisions have been assumed among distributors, each catering to a specific area with its own set of retailers. Mathematical expressions are developed to determine the optimal replenishment policies for the manufacturer, distributors, and retailers. Numerical examples are provided to illustrate the results, and sensitivity analysis is conducted to assess the model's responsiveness to parameter variations. Finally, managerial insights are discussed, shedding light on the implications and advantages of the proposed blockchainbased supply chain management system.